O complexo anorogênico plutono-vulcânico Salto da Divisa (ca. 900 Ma) e suas rochas encaixantes paleoproterozoicas (Complexo Buerarema) na fronteira Bahia-Minas - Anderson Magalhães Victoria (2023)
In tectonic terms, the southern region of the state of Bahia, bordering Minas Gerais, is inserted in the northeast portion of the Araçuaí belt, close to the limit with the São Francisco craton (SFC). This region is within the structural domain of the Itapebi Shear Zone, where the Brasiliano deformation developed along a NW-SE transpressive corridor, verging to the cratonic interior. A geological map (1:100.000) was prepared in an area of ca. 64,000 km², focusing on the rocks of the Salto da Divisa anorogenic complex and the related Rhyacian-Orosirian basement. These units were studied through petrographic, lithochemical, geochronological (LA-ICP-MS U-Pb, zircon) and isotopic geochemistry (Sm-Nd and Lu-Hf) analyses. The Salto da Divisa complex refers to a diverse set of plutonic, subvolcanic, and volcanic rocks, produced during the opening of the Macaúbas rift, in the early Tonian. The proposed petrogenetic model suggests the formation of a bimodal magmatism composed of ultramafic and mantlederived mafic swarm contemporaneous to the granitic, ferroan, A1-type- plutons. The granitogenesis, in turn, was heterogeneous and at least three petrological mechanisms were recognized: (i) partial melting of the continental crust; (ii) hybridization; and (iii) fractional crystallization. In addition, it was also verified the presence of hydrothermalized fluorite-amazonite-bearing two-mica leucogranites at the border and at cupola zones of some intrusions. Undersaturated alkaline trachytes and subalkaline rhyolites complete the magmatic set. As for the basement, a cartographic redefinition was carried out. In regional maps, the entire basement of the northeast portion of the Araçuaí belt, between the cities of Itapetinga and Eunápolis, is represented by the unit known as the Itapetinga complex, stretched along the NW-SE trend. In the mapped area, however, it is suggested that the basement represents the extension of the cratonic units that occur further north and that were reworked by the Neoproterozoic deformation during the Brasiliano event. Thus, the Itapetinga complex was redefined, representing the gneisses and migmatites that occur from the Itapetinga city to the western portion of the mapped area, around the Itarantim city. In the central part of the mapped area, the basement represents the extension of the unit known as the Ibicaraí complex, still without investigation and with an uncertain origin. To the east, it is suggested that the basement is the extension of the Buerarema complex, a Rhyacian unit (ca. 2.1 Ga) that represents a moderately juvenile introceanic arc developed during the pre-collisional set of the Minas-Bahia orogeny, which is the tectonic compressive event responsible for the construction of the São Francisco-Congo paleocontinent. Field, geochemical, and geochronological data show the presence of not previous mapped younger rocks (ca. 2.07 Ga and 2.03 Ga) intrusive within the Buerarema complex, which origin was interpreted as related to th